The iGreenGO Study: The Clinical Role of Indocyanine Green Imaging Fluorescence in Modifying the Surgeon’s Conduct During the Surgical Treatment of Advanced Gastric Cancer—Study Protocol for an International Multicenter Prospective Study - Lombardi, Pietro Maria; Mazzola, Michele; Nicastro, Vincenzo; Giacopuzzi, Simone; Baiocchi, Gian Luca; Castoro, Carlo; Rosati, Riccardo; Fumagalli Romario, Uberto; Bonavina, Luigi; Staderini, Fabio; Gockel, Ines; Gregori, Dario; et al. (Frontiers in Oncology, 2022)
Background: The near infra-red/indocyanine green imaging fluorescence (NIR/ICG) technology is showing promising results in several fields of surgical oncology. The clinical value of NIR/ICG technology in the surgical treatment of advanced gastric cancer (AGC) is not clearly established. Methods: This is the “iGreenGO” (indocyanine Green Gastric Observation) study protocol: a national prospective multicentre study. Western patients who undergo curative-intent gastrectomy with D2 lymphadenectomy for AGC constitute the study cohort. All the patients undergo preoperative upper gastrointestinal endoscopy for submucosal peritumoral ICG injection at the most 20 hours before surgery. Intraoperative endoscopic injection before starting surgical dissection is also allowed. The primary endpoint is the “change in the surgical conduct” (CSC) i.e. the need to perform further dissection after intraoperative NIR/ICG technology activation at the end of a D2 lymphadenectomy. Secondary endpoints include the pattern of abdominal fluorescence distribution according to tumor and patient characteristics, the preoperative clinical variables potentially associated with CSC and incidence of stage migration due to NIR/ICG application. Discussion: The iGreenGO study is be the first study to investigate the clinical role of NIR/ICG technology for surgical treatment of AGC in a large cohort of Western patients. Results from the present study can further clarify the role of the NIR/ICG technology in surgical lymphadenectomy for AGC.